1999
DOI: 10.1542/peds.104.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Deterioration in Previously Healthy Infants Hospitalized With Respiratory Syncytial Virus Infection

Abstract: Clinical deterioration requiring PICU admission is an uncommon occurrence in previously healthy infants admitted to a general pediatric inpatient unit with RSV infection. Extreme tachypnea and hypoxemia were both associated with subsequent deterioration; however, only a small proportion of patients who clinically deteriorated presented in this way. The clinical usefulness of these parameters, therefore, is limited. respiratory syncytial virus, deterioration, healthy infants, prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 10 publications
9
46
2
2
Order By: Relevance
“…Length of hospital stay was significantly shorter in the 3% hypertonic saline group, which is consistent with previous reports [16,[21][22][23][24][25][26]. The use of corticosteroids and antibiotics during hospitalization was similar in both groups, so these are unlikely to account for such difference.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Length of hospital stay was significantly shorter in the 3% hypertonic saline group, which is consistent with previous reports [16,[21][22][23][24][25][26]. The use of corticosteroids and antibiotics during hospitalization was similar in both groups, so these are unlikely to account for such difference.…”
Section: Discussionsupporting
confidence: 90%
“…Although several factors have been associated with an increased risk of severe disease, most infants with acute bronchiolitis admitted to the PICU are reported to be previously healthy and not considered of high risk [22,23]. The rate of patients with high risk factors admitted to the intensive care unit in our sample was 6.5% in the group receiving physiological saline and 3.1% in the group with 3% hypertonic saline, similar to that described in other series.…”
Section: Discussionsupporting
confidence: 85%
“…Hypoxemia is a primary indicator of disease in children with RSV (42). We previously hypothesized that hypoxemia could result from impaired AFC in RSV infection (4), and in this study we found that infection of mice with RSV resulted in mild hypoxemia in conscious mice on Day 2, when compared with matched preinfection Sm O 2 values.…”
Section: Effect Of Leflunomide On Hypoxemia In Rsv Infectionmentioning
confidence: 48%
“…By applying a threshold to a single clinical parameter, Brooks et al [55] built a model to predict whether an infant admitted to the general pediatric ward with RSV infection will be transferred to the ICU. In theory, this capability could support development of alternative care strategies, such as early use of NIPPV, for treating infants with RSV infection who present initially with milder symptoms.…”
Section: Predicting Icu Admissionmentioning
confidence: 99%